不同品种赤苍藤种仁营养成分及潜在应用价值分析 Analysis of nutritional components and potential application value of seed kernels of different varieties of Erythropalum scandens - 黄诗宇1，杨天为1，张向军1，张尚文1，黄松殿2，石前1，李婷1 HUANG Shiyu1,YANG Tianwei1,ZHANG Xiangjun1, ZHANG Shangwen1, HUANG Songdian2,SHI Qian1, LI Ting1 (Zhongguo youzhi)
旨在为开发利用赤苍藤种仁提供参考，以桂赤1号、桂赤2号赤苍藤种仁为实验原料，利用国标方法测定种仁粗脂肪、蛋白质、矿质元素含量，氨基酸组成，以及种仁油的脂肪酸组成，并评估氨基酸组成及含量合理性，考察种仁油的安全性，以此综合评价赤苍藤种仁的营养价值。结果表明：桂赤1号、桂赤2号种子的出仁率分别为52.88%、49.40%，种仁粗脂肪含量分别为50.37%、4843%，蛋白质含量分别为17.70%、18.23%，种仁中含有16种氨基酸，其中包含7种人体必需氨基酸，氨基酸比值系数分（SRC）值分别为63.29、63.85；赤苍藤种仁中钾、钙、镁、铁、锌含量较高，钠含量较低，各类矿质元素均衡，重金属元素含量未超过国家标准限量值；桂赤1号、桂赤2号种仁油的主要脂肪酸为油酸，其含量分别达80.03%、70.08%；2种赤苍藤种仁油的铅、苯并（a）芘、黄曲霉毒素B1、溶剂残留以及酸值和过氧化值均满足相关国标的限定要求。综上，桂赤2号种仁的蛋白质营养价值较高，而桂赤1号种仁的粗脂肪含量及种仁油的油酸含量相对更高，二者在保健食品、油料方面均具有较高的开发利用价值。 To provide a reference for the development and utilization of seed kernels of Erythropalum scandens, taking the seed kernels of Guichi No.1 and Guichi No.2 as experimental materials, the contents of crude fat, protein, mineral elements, and amino acid composition of the seed kernel, and fatty acid composition of the seed kernel oil, were determined by national standard methods. The rationality of the amino acid composition and content was evaluated, and the safety of the kernel oil was investigated. The nutritional value of Erythropalum scandens seed kernels was comprehensively evaluated. The results showed that the kernel yield of Guichi No.1 and Guichi No.2 seeds were 52.88% and 4940%, respectively. The crude fat content in seed kernels were 50.37% and 48.43%, respectively. The protein content was 17.70% and 18.23%, respectively. There were 16 amino acids in Erythropalum scandens seed kernels, including 7 essential amino acids and the SRC were 6329 and 6385, respectively. The contents of potassium, calcium, magnesium, iron and zinc in seed kernels of Erythropalum scandens were higher, while the content of sodium was lower. The mineral elements were balanced, and the heavy metal content did not exceed the national standard limits. The main fatty acid in the seed kernel oil of Guichi No.1 and Guichi No.2 was oleic acid, with contents of 80.03% and 7008%, respectively. The lead content, benzo(a)pyrene, aflatoxin B1, residucal solvent, as well as the acid value and peroxide value of the two types of Erythropalum scandens seed kernel oil all met the relative national standard limits, indicating a high level of safety. The seed kernel protein of Guichi No.2 has higher nutritional value, while the crude fat and oleic acid contents in the kernel oil of Guichi No.1 are relatively higher, and both have the development and utilization value in health food and oilseed.